2016
DOI: 10.1016/j.jacc.2016.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Crushed Prasugrel Tablets in Patients With STEMI Undergoing Primary Percutaneous Coronary Intervention

Abstract: In STEMI patients undergoing PPCI, crushed prasugrel leads to faster drug absorption, and consequently, more prompt and potent antiplatelet effects compared with whole tablet ingestion. (Pharmacological Effects of Crushing Prasugrel in STEMI Patients; NCT02212028).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 30 publications
1
60
0
2
Order By: Relevance
“…20- 22 In addition, previous studies of East Asian have suggested elevated therapeutic level of platelet reactivity following PCI or ACS, compared with reports from studies of Westerners. 13,20, 23 There is a paucity of data about platelet reactivity for Japanese STEMI patients within 2 h of loading, although PRASFIT-ACS demonstrated a 20-mg loading dose of prasugrel provided stronger platelet inhibition than clopidogrel at 2-4 h after loading in ACS patients. Moreover, a recent study reported that door-to-balloon time was almost 60 min, 24 and the incidence of intraprocedural thrombotic events was greater in patients with STEMI compared with non-ST-segment elevation ACS.…”
Section: Discussionmentioning
confidence: 99%
“…20- 22 In addition, previous studies of East Asian have suggested elevated therapeutic level of platelet reactivity following PCI or ACS, compared with reports from studies of Westerners. 13,20, 23 There is a paucity of data about platelet reactivity for Japanese STEMI patients within 2 h of loading, although PRASFIT-ACS demonstrated a 20-mg loading dose of prasugrel provided stronger platelet inhibition than clopidogrel at 2-4 h after loading in ACS patients. Moreover, a recent study reported that door-to-balloon time was almost 60 min, 24 and the incidence of intraprocedural thrombotic events was greater in patients with STEMI compared with non-ST-segment elevation ACS.…”
Section: Discussionmentioning
confidence: 99%
“…18 In STEMI patients undergoing primary PCI delayed antiplatelet effects of oral P2Y 12 inhibitors, including prasugrel, have been observed. Rollini et al 19 investigated the bioavailablity of crushed prasugrel tablets vs. whole prasugrel tablets. The study showed that compared with whole tablets, crushed prasugrel led to reduced P2Y 12 reaction units by 30 min post-loading dose, which persisted at 1, 2, and 4 h post-loading dose.…”
Section: P2y 12 Inhibitorsmentioning
confidence: 99%
“…Similarly, in a larger study, involving 108 STEMI patients treated with prasugrel, platelet reactivity at the end of primary PCI was 90.1 units in those who received morphine compared with 43.5 units in patients who did not (P<0.001). 15 On the other hand, in the CRUSH study (Pharmacological Effects of Crushing Prasugrel in STEMI Patients), 16 differences regarding the pharmacokinetic profile of the active metabolite of prasugrel were statistically nonsignificant with or without morphine, regardless of whether crushed or whole tablets were administered, both in terms of total exposure (P=0.198 and 0.286, for whole and crushed tablets, respectively) and exposure over the first 2 hours (P=0.459 and 0.776, for whole and crushed tablets, respectively) to the active metabolite. These findings are certainly hypothesis generating; however, the small sample size, the nonrandomized use of morphine, and the secondary or post hoc nature of most of these observations raise some doubt as to the true significance of the morphine effect on P2Y 12 receptor antagonist effectiveness in real life.…”
Section: Prasugrel and Ticagrelormentioning
confidence: 99%